Implementation of REDD+ in the existing forest property rights: lessons from Berau, East Kalimantan Province, Indonesia. (May 2019) - Rochmayanto, Y; Nurrochmat, D R; Nugroho, B; Darusman, D; Satria, A
Abstract: There is a little empirical evidence on how REDD+ can work through existing property rights that define Indonesian forests. This article focuses on assessing the effectiveness of existing forest property rights in local forest institutions within a REDD+ framework. The study focuses on two local forest institutions: Forest Management Unit (FMU) of Berau Barat, and Merabu Village Forest. Within these forest landscapes, households within three villages were selected for interview and household survey collection. This research first examines the bundle of rights allotted to households by examining the content of formal rules enacted for Forest Management Units and Village Forests. Specifically, these different forest property types were assessed for the ability of local forest institutions to control additionality, leakage, and permanence. The results of formal policy were then compared to data collected from households within the forest landscape of Berau, East Kalimantan. This comparison finds that Merabu Village Forest provides higher forest tenure security than the FMU of Berau Barat. Further, forest rights from Merabu Village Forest are more likely to promote REDD+ outcomes, indicated by the ability for local authority to control additionality, leakage, and permanence. Finally, this research finds increasing capacity to manage leakage, integrate national and local tenure efforts, include local knowledge, law enforcement capacity, and community awareness.